2012
DOI: 10.1007/s10995-012-1123-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Race and Socioeconomic Status to Postpartum Depressive Symptoms in Rural African American and Non-Hispanic White Women

Abstract: This study examines the potential racial disparity in postpartum depression (PPD) symptoms among a cohort of non-Hispanic white and African American women after taking into consideration the influence of socioeconomic status (SES). Participants (N = 299) were recruited from maternity clinics serving rural counties, with over-sampling of low SES and African Americans. The Edinburgh Postnatal Depression Scale (EPDS) was administered 1 and 6 months postpartum, and subjective SES scale at 6 months postpartum. Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 35 publications
5
60
2
Order By: Relevance
“…In the specific cultural groups of the U.S, the reported prevalence vary within 4.6-10.7 % in Asian-American [106,107], 6.4-16.7 % in Hispanic [107,108], 3.7-20.7 % in African-American and 2.6-14.8 % in Caucasian [107][108][109].…”
Section: Ppd In Usamentioning
confidence: 94%
See 2 more Smart Citations
“…In the specific cultural groups of the U.S, the reported prevalence vary within 4.6-10.7 % in Asian-American [106,107], 6.4-16.7 % in Hispanic [107,108], 3.7-20.7 % in African-American and 2.6-14.8 % in Caucasian [107][108][109].…”
Section: Ppd In Usamentioning
confidence: 94%
“…Caucasian women, compared with other cultural groups, have the lowest risk for PPD [107][108][109] and a greater chance for their disease to be diagnosed by professionals of mental health [107].…”
Section: Ppd In Usamentioning
confidence: 99%
See 1 more Smart Citation
“…While some researchers have found the rates of postpartum depression to be higher in rural areas (Villegas, McKay, Dennis, & Ross, 2011), others have reported the prevalence to be higher in urban areas (Clare & Yeh, 2012). Likewise, various researchers have found differences among racial and ethnic groups (Gress-Smith, Luecken, Lemery-Chalfant, & Howe, 2012; Savitz, Stein, Ye, Kellerman, & Silverman, ADVANCES IN SOCIAL WORK, Fall 2015, 16 (2) 204 2011) and the likelihood that the rates for low-income mothers and for mothers of color are higher than estimated (CDC, 2008;Dolbier, et al, 2013;Gress-Smith et al, 2012;Lara et al, 2015).…”
Section: The Varying Rates Of Postpartum Depressionmentioning
confidence: 99%
“…While some researchers have found the rates of postpartum depression to be higher in rural areas (Villegas, McKay, Dennis, & Ross, 2011), others have reported the prevalence to be higher in urban areas (Clare & Yeh, 2012). Likewise, various researchers have found differences among racial and ethnic groups (Gress-Smith, Luecken, Lemery-Chalfant, & Howe, 2012; Savitz, Stein, Ye, Kellerman, & Silverman, ADVANCES IN SOCIAL WORK, Fall 2015, 16 (2) 204 2011) and the likelihood that the rates for low-income mothers and for mothers of color are higher than estimated (CDC, 2008;Dolbier, et al, 2013;Gress-Smith et al, 2012;Lara et al, 2015).Some researchers have suggested that mothers of color face more elevated rates of postpartum depression than White mothers because of greater life stressors, including economic factors known to affect postpartum depression. To date, research has concluded that compared to White mothers and mothers from privileged backgrounds, mothers of color have lower incomes (Dagher, McGovern, Dowd, & Gjerdingen, 2012;Feder et al, 2009;Kozinsky et al, 2012;Lara et al, 2015), lower levels of education (Dagher et al, 2012;Lanes, Kuk, & Tamim, 2011), higher rates of unemployment (Boyce & Hickey, 2005;Dagher et al, 2012;Janssen, Heaman, Urquia, O'Campo, & Thiessen, 2012), greater likelihood of single parenting (Boyce & Hickey, 2005;Lewin, Mitchell, & Ronzio, 2013), and worse housing conditions (Cutrona et al, 2005;Jacobs, 2011;Redshaw & Henderson, 2013).…”
mentioning
confidence: 99%